Postpartum Headache—Unmasking the Zebra Among the Horses: A Case Report. Issue 3 (November 2020) - Jones, Anastasia; Cometa, M. Anthony; Euliano, Tammy; Lopez, Brandon M.
Abstract : Postdural puncture headache (PDPH) is a complication of dural puncture. An epidural blood patch (EBP) is the standard treatment; however, when EBP fails, alternative treatments and/or diagnoses must be considered. We present a case of orthostatic headache initially diagnosed as PDPH but likely due to spontaneous intracranial hypotension. It is imperative for anesthesiologists, as members of an interdisciplinary peripartum team, to be familiar with the evaluation and treatment of postpartum headache and recognize when further workup and consultation may be indicated.